A novel approach to ambient energy (thermoelectric, piezoelectric and solar-TPS) harvesting: Realization of a single structured TPS-fusion energy device using MAPbI3. (October 2018) - Jella, Venkatraju; Ippili, Swathi; Eom, Ji-Ho; Kim, Yun-Jeong; Kim, Hye-Jin; Yoon, Soon-Gil
Abstract: Organic-inorganic lead halide perovskite (MAPbI3 ) has shown remarkable photovoltaic performance along with unique properties such as ambipolar nature, ferroelectric and ultra-high Seebeck coefficient with low thermal conductivity. The exclusive properties of MAPbI3 enable to use as a fusion energy conversion material for harvesting of ambient energy such as the thermal, mechanical and solar energy. Many researchers have focused on each of these topics separately. This paper demonstrates a flexible single structured TPS-fusion energy device comprising of interdigitated electrodes (IDEs) and MAPbI3 to harvest thermal, mechanical and solar energy. A TPS-device is individually operated as a thermoelectric, piezoelectric, and solar (TPS)-energy harvester by independently applying a thermal gradient, mechanical force and solar energy. The TPS-device as a thermoelectric generator is exhibited the higher thermoelectric output performance in in-plane temperature gradient than out-of-plane temperature gradient. The obtained piezoelectric output values of the TPS-device as a piezoelectric generator under periodic applied pressure are 1.47 V and 0.56 µA. The TPS-based photovoltaic device is generated an open-circuit voltage of 0.77 V and a short-circuit current density of 0.022 mA/cm 2 . This conceptual demonstration of fusion energy harvesting device using IDE-based structure with light active ambipolar material could introduce innovative approaches in fusion-conversion energy technology. Graphical abstract: Demonstration of a flexible single structured TPS-fusion energy device comprising of interdigitated electrodes (IDEs) with charge transport layers and MAPbI3 to harvest thermal, mechanical and solar energy from ambient energy sources. A TPS-device is successfully operated as a thermoelectric, piezoelectric, and solar (TPS)-energy harvester by independently applying a thermal gradient, mechanical force, and sun light. fx1 Highlights: A flexible single structured TPS-fusion energy device composed of Interdigitated electrodes (IDEs) and MAPbI3 perovskite. TPS-device as multiple energy harvesters such as thermoelectric, piezoelectric and solar energy harvester. Light active ambipolar MAPbI3 acts as fusion energy conversion material. Charge transport layers (ZnO and Cu2O-IDE) effect on TPS-device operation and its output performance.